Customers satisfaction towards the services provided in Kuala Lumpur International Airport, Malaysia - Abdul, Mohani; Abdul Aziz, Mohd Khairi; Yahya, Mastora (David Publishing, 2015)
This study is conducted to measure customers satisfaction from the five dimensions of service quality, which are empathy, tangibility, responsiveness, reliability, and assurance. A quantitative approach, using the gap-model—SERVQUAL, has been used in the survey to gauge the opinions of Kuala Lumpur International Airport (KLIA) customers chosen via convenient sampling. Based on 100 respondents picked from several parts of the airport, the self-administered questionnaires were distributed and collected on the same day. Statistical tests such as multiple regression and ANOVA were performed and the results obtained among others showed that tangible elements of KLIA are the most important determinant of customers satisfaction followed by the intangible elements such as empathy, responsiveness, assurance, and reliability. The results of this study will be helpful to the management of KLIA in their effort to continuously upgrade their services in improving the customer services.